Graft copolymers for reducing interfacial tension in polymer blends

By adopting graft copolymers with specific structures, controlling their molecular weight and number of graft branches, optimizing the distribution in the polymer mixture, solving the problem of insufficient phase boundary tension between polymer mixtures in the prior art, and achieving high compatibility and stable processing of the composite.

JP2025510925APending Publication Date: 2025-04-15COVESTRO DEUTSCHLAND AG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024557228
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-04
Filing Date
2023-03-29
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art lacks the effect of reducing the phase boundary tension between polymer mixtures of various chemical components, resulting in problems such as phase separation and instability of polymer composites during thermoplastic processing.

Method used

A graft copolymer with a specific structure is used, which consists of two polymers of different chemical components, one of which is a polyamide polymer and the other is one or more different styrene copolymers. By controlling the molecular weight of the graft copolymer and the number of graft branches, its distribution in the polymer mixture is optimized, thereby reducing the phase boundary tension.

Benefits of technology

It effectively reduces the phase boundary tension between polymer mixtures, improves the compatibility and processing stability of the composites, and reduces the problems of surface defects and insufficient mechanical properties of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510925000028
    Figure 2025510925000028
  • Figure 2025510925000029
    Figure 2025510925000029
  • Figure 2025510925000001
    Figure 2025510925000001
Patent Text Reader

Abstract

The present invention relates to a polymer having the general structure B-(A) consisting of two polymer blocks A and B having different chemical composition. ns The present invention relates to a graft copolymer of the above-mentioned polymers, in which one of the polymers is a polycondensation polymer selected from the group consisting of polycarbonates, polyester carbonates, polyesters, and polyamides, and the other polymer is a polymerization product of at least one vinyl monomer. n (B) is equal to at least 13 kg / mol, as determined by a combination of gel permeation chromatography and NMR spectroscopy; and (ii) the number of side chains in the graft copolymer, n s is determined by NMR spectroscopy and is at least equal to 3 and at most equal to 15; and (iii) the average molecular weight M of the blocks of polymer A. n (A) is equal to at least 1.5 kg / mol and at most 15 kg / mol, as determined by a combination of gel permeation chromatography and NMR spectroscopy; and (iv) n s M n The present invention also relates to the use of the above-mentioned graft copolymer for reducing the phase surface tension in a mixture containing polymers A and B, a composition containing the graft copolymer and polymers A and B, and a molded body containing the composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to graft copolymers of a particular structure consisting of two blocks of polymers A and B of different chemical composition, one of which is a polycondensation polymer selected from the group consisting of polycarbonates, polyestercarbonates, polyesters and polyamides, and the other polymer is a polymer of one or more different vinyl monomers. The invention further relates to the use of these graft copolymers to reduce the interfacial tension between phases in mixtures containing homopolymers A and B or mixtures of polymers of similar polarity, to compositions containing the graft copolymers and homopolymers A and B or polymers of similar polarity, to molding compounds made from such compositions, and to molded articles made from these molding compounds. [Background technology]

[0002] Mixtures of immiscible polymers of different chemical composition are sometimes suitable for the production of multiphase polymer blends with properties that synergistically combine the specific use advantages of the two polymers. However, if the difference in polarity of polymers A and B is too large, i.e., if the interfacial tension at the phase interface of the two polymers is too large, the polymer blend is prone to phase separation. The resulting rough and / or unstable phase morphology or poor phase adhesion often leads to undesirable effects such as poor light transmission, phase delamination, poor processing stability, inadequate mechanical properties (e.g. material ductility / toughness, elongation at break, resistance to stress cracking or weld line strength), cosmetic surface defects on injection molded parts formed from the polymer blends through thermoplastic processing processes, especially in the case of high shear, or removal of decorative layers applied on the injection molded parts. In such cases, in order to achieve the desired technical property profile, it is often necessary to add a compatibilizer to the polymer blend composition that reduces the interfacial tension between the polymers forming the blend, thereby reducing or ideally eliminating the above-mentioned technical problems altogether.

[0003] Mixtures of polymers of different chemical composition are also suitable for the production of block copolymers consisting of blocks of chemically different polymer species by reacting the two polymers with each other in a multiphase melt of the polymer mixture. Since such reactions can by definition only occur at the phase interface of different polymers in the melt, the reaction rate of such melt reactions depends on the size of the phase interface, i.e., the size of the phase dispersion, or the domain size of the different polymers in the molten mixture. Therefore, in order to achieve high levels of conversion within technically possible or reasonable reaction residence times, a thermodynamically stable finely divided phase morphology in the melt is necessary, and a reduction in the interfacial tension between the different polymers in the molten mixture, i.e., the use of a compatibilizer as a process aid, is often required.

[0004] Past experience has demonstrated the suitability of block copolymers consisting of blocks of polymers A and B as compatibilizers in polymer mixtures composed of two chemically different polymers A and B, and the common understanding based on experience in the emulsification of immiscible low-viscosity liquids is that bipolar AB block copolymer structures generally appear particularly attractive to those skilled in the art in terms of achieving a high degree of effectiveness for the intended purpose. However, such block copolymer structures are difficult to synthesize in the case of block copolymers that contain a polycondensation polymer as block A and a vinyl (co)polymer as block B. A generally more readily available synthetic option are graft copolymers consisting of blocks of polycondensation polymer and vinyl (co)polymer.

[0005] For example, US Pat. No. 5,999,333 discloses a process for preparing copolymers by reaction of glycidyl methacrylate grafted olefin polymers with carboxy-functionalized polycarbonates in organic solutions or in melt compounding, and the use of such copolymers, apparently graft copolymers, for compatibilization of polycarbonate-polyolefin polymer blends with the aim of reducing their delamination tendency. The application makes no mention of the effect of the spatial arrangement of the grafted arms on the number of grafted backbones / grafted arms, or the effect of the length of the grafted arms and grafted backbones on the effectiveness of the grafted copolymers as compatibilizers in polymer blends.

[0006] Prior art graft copolymers are ineffective at reducing the interfacial tension between the phases in the blends or melt mixtures of polymers A and B from which they are formed.

[0007] Patent Document 2 describes a polymer consisting of free radical generating polymers as blocks A and B, preferably having an average molecular weight M of 20,000 g / mol to 100,000 g / mol. n (A) is preferably a polymer having an average molecular weight M of more than 50,000 g / mol, with n=2 to 8 graft branches. n B-(A) consists of a polymer B having (B) grafted onto its backbone, n The present invention discloses a graft copolymer having a structure, the relative block length being n M n (A) / (n M n (A)+M n (B)) is preferably selected to be in the range of 0.6 to 0.8. The application discloses that these graft copolymers are suitable for impact modification of transparent polymers. The application is silent about their effect as compatibilizers in blends of homopolymers A and B.

[0008] Patent Document 3 discloses a polypropylene / polylactic acid ion-grafted copolymer with high toughness and its manufacturing process. The process provided by this invention is simple and low-cost, and uses anionic and cationic interactions to graft polylactic acid onto the backbone. There is no disclosure of its effect as a compatibilizer.

[0009] US Patent No. 5,399,633 discloses a process for forming polycarbonate graft copolymers. More specifically, a polycarbonate polymer or copolymer containing allyl groups constitutes the backbone of the graft copolymer, and side chains are attached to the copolymer via the allyl groups. The graft copolymers exhibit a combination of high transparency, good levels of grafting, good scratch resistance and / or good anti-fog properties. This disclosure also does not show any effect on phase compatibility.

[0010] Patent Document 5 discloses an optical resin composition mainly comprising a graft copolymer containing a styrene resin and an aromatic polycarbonate, each of which has a specific molecular weight and a specific ratio of molecular weight to weight, and the composition has a microdispersed phase of 0.5 μm or less. The resin composition is suitable for optical applications. There is no disclosure of phase compatibilization.

[0011] Patent Document 6 discloses a film having a layer composed of a graft copolymer of polyester and acrylic polymer. This layer ensures good lubricity and printability. There is no disclosure about the effect of the graft copolymer as a phase compatibilizer. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] U.S. Patent No. 4,959,411 [Patent Document 2] US Patent Application Publication No. 2006 / 063891 [Patent Document 3] China Patent Application Publication No. 108586668 [Patent Document 4] US Patent Application Publication No. 2012 / 071606 [Patent Document 5] U.S. Patent No. 488401 [Patent Document 6] Japanese Patent Application Publication No. 09-143293 Summary of the Invention [Problem to be solved by the invention]

[0013] The basis of the present invention was the desire to provide special graft copolymers that show improved effectiveness in lowering the interfacial tension of polymer blends and / or reactive melt mixtures composed of polymers A and B of different chemical composition under comparable conditions, i.e. using the same concentrations of material, as additives or process aids, where one of the polymers is a polycondensation polymer selected from the group consisting of polycarbonates, polyestercarbonates, polyesters, polyamides, and mixtures thereof, and the other polymer is a polymer composed of one or more different vinyl monomers. The vinyl monomers are preferably selected from the group consisting of styrene, styrene derivatives, vinyl cyanides, acrylic esters, acrylic ester derivatives, olefins, maleimides, and maleimide derivatives. The final objective is that these graft copolymers can thereby contribute to an improved solution to at least one of the abovementioned technical problems resulting from the poor compatibility of polymers A and B.

[0014] In the context of the present invention, the variable E=(1-γ / γ0) serves as a measure of the reduction in interfacial tension and is called the compatibilizer efficiency. In this specification, γ0 is the interfacial tension of a non-compatibilized polymer blend composed of homopolymers A and B, i.e. the interfacial tension at the phase interface of such polymers in the absence of the graft copolymer, and γ is the value of the interfacial tension reduced by the addition of the graft copolymer. If the graft copolymer is completely ineffective as a compatibilizer, then γ=γ0 and therefore E=0. In the other extreme case of best compatibilization, the interfacial tension at the phase interface of homopolymers A and B in the presence of the graft copolymer is reduced to a value γ=0, i.e. complete miscibility is achieved. Therefore, in this case, E=1. The value of the compatibilizer efficiency E depends, by definition, on the concentration of the graft copolymer used. In the context of the present invention, under the conditions used in the experiments that serve as its basis, a minimum value of 30, preferably a minimum value of 35, even more preferably 40, and even more preferably 45 was considered desirable. It is also desirable that these graft copolymers exert their effective effect at the lowest possible molecular weight of the graft copolymer used, since graft copolymers having excessively high molecular weights have lower diffusion coefficients in the polymer melt and therefore, for kinetic reasons, are less likely (i.e., slower) to migrate to interfaces of polymer components in the polymer blend to effectively exert the desired effect. [Means for solving the problem]

[0015] The object of the present invention is to provide a polymeric polymer having the general structure B-(A) consisting of two polymer blocks A and B of different chemical composition. ns wherein one of the polymers, preferably polymer A, is a polycondensation polymer selected from the group consisting of polycarbonates, polyestercarbonates, polyesters and polyamides, and the other polymer, preferably polymer B, is a polymer composed of at least one vinyl monomer, (i) Number average molecular weight M of the block of polymer B n(B) is at least 13 kg / mol, as determined by a combination of gel permeation chromatography and NMR spectroscopy; (ii) The number of side chains in the graft copolymer, n s is at least 3 and not more than 15, as determined by NMR spectroscopy; (iii) Number average molecular weight M of the block of polymer A n (A) is at least 1.5 kg / mol and not more than 15 kg / mol, as determined by a combination of gel permeation chromatography and NMR spectroscopy; (iv)n s M n Multiplying by (A) will result in at least 13 kg / mol. This is achieved by the graft copolymer, which is characterized by:

[0016] Different individual n s In the case of a mixture of graft copolymer molecules having a value, the preferred ranges, embodiments, and claims of the present invention are s " is generally the n of individual polymer molecules s Refers to the number average arithmetic mean of the values.

[0017] n s The value of is preferably at least 4, more preferably at least 5, and most preferably at least 6.

[0018] M n (A) is preferably at least 3.0 kg / mol, more preferably at least 4.5 kg / mol, and most preferably at least 5.3 kg / mol.

[0019] M n (B) is preferably at least 20 kg / mol, more preferably at least 23 kg / mol, and most preferably at least 30 kg / mol.

[0020] n s ×M nThe value of (A) is preferably at least 20 kg / mol, more preferably at least 30 kg / mol, and most preferably at least 35 kg / mol.

[0021] n s The value of is preferably 12 or less, further preferably 10 or less, and further preferably 8 or less.

[0022] M n The value of (B) is preferably 200 kg / mol or less, more preferably 100 kg / mol or less, and even more preferably 50 kg / mol or less.

[0023] M n The value of (A) is preferably 12 kg / mol or less, preferably 9 kg / mol or less, more preferably 8 kg / mol or less.

[0024] n s M n The value multiplied by (A) is preferably 120 kg / mol or less, more preferably 80 kg / mol, and even more preferably 50 kg / mol.

[0025] M n (A)×n s / [M n (B)+M n (A)×n s ] is preferably in the range of 0.25 to 0.75, more preferably in the range of 0.40 to 0.70, and even more preferably in the range of 0.40 to 0.60.

[0026] n s , M n (A), M n (B), and s ×M n (A) Upper and Lower Limits, and M n (A)×n s / [M n (B)+M n (A)×n s ] are all possible combinations of ranges.

[0027] In particular, graft copolymers characterized by the following combination of properties are preferred: (i) M n (B) is at least 23 kg / mol; (ii)n s At least 5, (iii) M n (A) is at least 3.0 kg / mol, and (iv)n s M n Multiplying by (A) gives at least 13 kg / mol.

[0028] Particularly preferred graft copolymers are characterized by the following combination of properties: (i) M n (B) is at least 23 kg / mol; (ii)n s At least 6, (iii) M n (A) is at least 4.5 kg / mol, and (iv)n s M n Multiplying by (A) gives at least 13 kg / mol.

[0029] The most preferred graft copolymers are characterized by the following combination of properties: (i) M n (B) is at least 23 kg / mol; (ii)n s At least 6, (iii) M n (A) is at least 4.5 kg / mol; (iv)n s M n (A) is at least 13 kg / mol, and (v) M n (A)×n s / [M n (B)+M n (A)×n s ] is in the range of 0.40 to 0.70.

[0030] The graft copolymers of the present invention may furthermore differ with respect to their structure, i.e., the spatial distribution of the grafted branches on the graft copolymer backbone. The grafting of the grafted branches on the graft copolymer backbone may exhibit a random distribution herein ("randomly grafted"). Likewise, it is also possible (i) to arrange the grafted branches uniformly and equidistantly on the graft copolymer backbone ("uniformly equidistant grafted"). Furthermore, it is also possible (ii) to arrange the grafted branches completely at one end of the graft copolymer backbone ("single-end grafted"), (iii) to arrange the grafted branches at both ends of the graft copolymer backbone ("double-end grafted"), or (iv) to arrange the grafted branches in the center of the graft copolymer backbone of the graft copolymer ("center grafted"). Structures (i) to (iv) are shown diagrammatically in FIG. 1.

[0031] The graft copolymers of the present invention are preferably center grafted or both end grafted, more preferably center grafted.

[0032] Structures (ii), (iii), and (iv) have a graft copolymer backbone that includes portions with grafted arms and portions without grafted arms. In the present specification, preferred are graft copolymers that include a graft copolymer backbone having a mass fraction of 50% by weight or less, more preferably 40% by weight or less, and even more preferably 30% by weight or less of the graft copolymer backbone, in total, including the portions with grafted arms.

[0033] Polymers composed of vinyl monomers are also called vinyl (co)polymers in the context of the present invention.

[0034] Block B is also called in the context of the present invention the graft copolymer backbone, the graft copolymer backbone or the backbone. Block A is called the side chain or the graft branch.

[0035] The at least one vinyl monomer is preferably selected from the group consisting of styrene, styrene derivatives, vinyl cyanides, acrylates, acrylate derivatives, olefins, maleimides and maleimide derivatives.

[0036] The blocks of polymers A and B are preferably polar and more preferably have a similar chemical structure to the polymers forming the polymer blend or polymer melt mixture for which a reduction in interfacial tension is desired, i.e. the combination of polymers of blocks A and B preferably has a Flory-Huggins parameter similar to the combination of polymers forming the polymer blend or polymer melt mixture for which a reduction in interfacial tension is desired.

[0037] It is further preferred that the blocks consist of the same polymers A and B which are also present in the polymer blend or polymer melt mixture for which a reduction in interfacial tension is desired. The phrase "of the same polymers A and B" refers to the chemical structure but not necessarily the molecular weight.

[0038] Polycondensation Polymer One of the polymers forming the graft copolymer of the invention, preferably polymer A, is a polycondensation polymer selected from the group consisting of polycarbonates, polyestercarbonates, polyesters and polyamides. It is also possible to use a mixture of different polycondensation polymers with similar polarity and chemical structure, such as a mixture of structurally different, preferably aromatic, polycarbonates, preferably aromatic polyestercarbonates or preferably aromatic polyesters, preferably a mixture of structurally different, preferably aromatic polycarbonates, or a mixture of structurally different, preferably aromatic polyestercarbonates, or a mixture of structurally different, preferably aromatic polyesters, more preferably a mixture of structurally different, preferably aromatic polycarbonates.

[0039] The polycarbonates and / or polyestercarbonates corresponding to component A suitable according to the invention are known from the literature or can be prepared by processes known from the literature (for the preparation of polycarbonates see, for example, Schnell, "Chemistry and Physics of Polycarbonates", Interscience Publishers, 1964 and also DE-A-1 495 626, DE-A-2 232 877, DE-A-2 703 376, DE-A-2 714 544, DE-A-3 000 610, DE-A-3 832 396; for the preparation of polyestercarbonates see, for example, DE-A-3 007 934).

[0040] Polycarbonates are produced, for example, by reacting at least one aliphatic and / or aromatic diol (diphenol) with a carbonyl halide, preferably phosgene, and / or preferably an aromatic dicarbonyl dihalide, preferably a benzene dicarbonyl dihalide, by an interfacial process, optionally using a chain terminator, for example a monophenol, and optionally using a trifunctional or higher branching agent, for example a triphenol or a tetraphenol. Mixtures of aliphatic and aromatic diols can also be used. Production via melt polymerization processes by reaction of aliphatic and / or aromatic diols (diphenols) with, for example, diphenyl carbonate is also possible.

[0041] The diphenols for the preparation of the aromatic polycarbonates and / or aromatic polyester carbonates preferably have the formula (1): [ka] (In the formula, A is a single bond, C1-C5 alkylene, C2-C5 alkylidene, C5-C6 cycloalkylidene, -O-, -SO-, -CO-, -S-, -SO2-, C6-C alkylene optionally fused with a further aromatic ring containing a heteroatom. 12Arylene, or Formula (2) or Formula (3): [ka] Based on B is, in each case, C1 to C 12 alkyl, preferably methyl; halogen, preferably chlorine and / or bromine; x, at each occurrence, is independently 0, 1, or 2; p is 1 or 0, and R 5 and R 6 For each X 1 can be individually selected, each independently being hydrogen or C1-C6 alkyl, preferably hydrogen, methyl, or ethyl; X 1 is carbon, and m is an integer from 4 to 7, preferably 4 or 5, provided that at least one atom X 1 R on top 5 and R 6 is a diphenol of the formula (wherein each is an alkyl group).

[0042] Preferred diphenols are hydroquinone, resorcinol, dihydroxydiphenols, bis(hydroxyphenyl) C1-C5 alkanes, bis(hydroxyphenyl) C5-C6 cycloalkanes, bis(hydroxyphenyl) ethers, bis(hydroxyphenyl) sulfoxides, bis(hydroxyphenyl) ketones, bis(hydroxyphenyl) sulfones, and α,α-bis(hydroxyphenyl) diisopropylbenzene, and their ring brominated and / or ring chlorinated derivatives.

[0043] Particularly preferred diphenols are 4,4'-dihydroxydiphenyl, bisphenol A, 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfone, and their dibrominated or dichlorinated and tetrabrominated or tetrachlorinated derivatives, such as 2,2-bis(3-chloro-4-hydroxyphenyl)propane, 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane, or 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane. 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) is particularly preferred.

[0044] The diphenols can be used individually or in the form of any desired mixtures. The diphenols are known from the literature or can be obtained by literature processes.

[0045] Suitable aliphatic diols are cyclohexane-1,2-diol, cyclohexane-1,3-diol, cyclohexane-1,4-diol, cyclohexane-1,2-dimethanol, cyclohexane-1,3-dimethanol, cyclohexane-1,4-dimethanol, 2,2-bis(4-hydroxycyclohexyl)propane, tetrahydrofuran-2,5-dimethanol, 2-butyl-2-ethylpropane-1,3-diol, 2-(2-hydroxyethoxy)ethanol, 2,2,4,4-tetramethylcyclobutane-1 ,3-diol, 2,2,4-trimethylpentane-1,3-diol, 2,2-dimethylpropane-1,3-diol, cyclobutane-1,1-diyldimethanol, 8-(hydroxymethyl)-3-tricyclo[5.2.1.02,6]decanyl]methanol, propane-1,2-diol, propane-1,3-diol, butane-1,4-diol, pentane-1,5-diol, hexane-1,6-diol, octane-1,8-diol, isosorbide and any desired mixtures thereof.

[0046] Examples of chain terminators suitable for the preparation of thermoplastic aromatic polycarbonates include phenol, p-chlorophenol, p-tert-butylphenol or 2,4,6-tribromophenol, as well as long-chain alkylphenols, such as 4-[2-(2,4,4-trimethylpentyl)]phenol, 4-(1,3-tetramethylbutyl)phenol according to DE-A-2842005, or mono- or dialkylphenols having a total of 8 to 20 carbon atoms in the alkyl substituent, such as 3,5-di-tert-butylphenol, p-isooctylphenol, p-tert-octylphenol, p-dodecylphenol, as well as 2-(3,5-dimethylheptyl)phenol and 4-(3,5-dimethylheptyl)phenol. The amount of chain terminator used is generally between 0.5 mol% and 10 mol% relative to the total moles of the diphenols used in each case.

[0047] Thermoplastic aromatic polycarbonates can be branched in a known manner by incorporating trifunctional or more than trifunctional compounds, for example compounds having three or more phenolic groups, however, it is preferred to use linear polycarbonates, more preferably linear polycarbonates based on bisphenol A.

[0048] Both homopolycarbonates and copolycarbonates are suitable. The copolycarbonates of the invention corresponding to component A can also be prepared using polydiorganosiloxanes having 1% to 25% by weight, preferably 2.5% to 25% by weight, of hydroxyaryloxy end groups, based on the total amount of diols used. These are known (US Pat. No. 3,419,634) and can be prepared by known literature processes. The preparation of polydiorganosiloxane-containing copolycarbonates is described, for example, in DE-A-3334782 and WO-A-2015 / 052106.

[0049] Also, the following structure: [ka] Also preferred are copolycarbonates prepared using the diphenols In the formula, R1 is hydrogen, C1-C4 alkyl, preferably hydrogen or methyl, particularly preferably hydrogen; R2 is independently aryl or alkyl, preferably methyl; X is a single bond, -SO2-, -CO-, -O-, -S-, C1 to C6 alkylene, C2 to C5 alkylidene or C6 to C 12 arylene, optionally fused to a further aromatic ring containing a heteroatom; X is preferably a single bond, C1 to C5 alkylene, C2 to C5 alkylidene, C5 to C 12 X is preferably a single bond, isopropylidene, C5 to C6 12 cycloalkylidene or oxygen, very particularly preferably isopropylidene, n is an average number of 10 to 400, preferably 10 to 100, particularly preferably 15 to 50; m is an average number of 1 to 10, preferably 1 to 6, and particularly preferably 1.5 to 5.

[0050] The aromatic dicarbonyl dihalides for the preparation of aromatic polyester carbonates are preferably the diacyl dichlorides of isophthalic acid, terephthalic acid, diphenyl ether 4,4'-dicarboxylic acid and naphthalene-2,6-dicarboxylic acid. Particularly preferred are mixtures of the diacyl dichlorides of isophthalic acid and terephthalic acid in a ratio of between 1:20 and 20:1.

[0051] In the preparation of polyester carbonates, a carbonyl halide, preferably phosgene, is additionally used in combination as a difunctional acid derivative.

[0052] Useful chain terminators for the preparation of aromatic polyester carbonates include, in addition to the monophenols already mentioned, their chlorocarbonates and, optionally, C1-C 22 Acyl chlorides of aromatic monocarboxylic acids which may be substituted with alkyl or halogen atoms, and aliphatic C2-C 22 Monocarbonyl chloride is an example.

[0053] The amount of chain terminator is in each case 0.1 mol % to 10 mol % relative to the number of moles of diphenol in the case of phenolic chain terminators and relative to the number of moles of dicarbonyl dichloride in the case of monocarbonyl chloride chain terminators.

[0054] For the preparation of the aromatic polyester carbonates it is furthermore possible to use one or more aromatic hydroxycarboxylic acids.

[0055] The aromatic polyestercarbonates can be linear or branched in a known manner (see DE-A-2 940 024 and DE-A-3 007 934), but linear polyestercarbonates are preferred.

[0056] The branching agents used are trifunctional or polyfunctional carbonyl chlorides, such as trimesoyl trichloride, cyanuric trichloride, 3,3',4,4'-benzophenone tetracarbonyl tetrachloride, 1,4,5,8-naphthalene tetracarbonyl tetrachloride or pyromellitic tetrachloride, or trifunctional or polyfunctional phenols, such as phloroglucinol, 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)hept-2-ene, 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)heptane, 1,3,5 ... The branching agent may be 1,4-bis[4,4'-dihydroxytriphenyl)methyl]benzene, 1,1,1-tri(4-hydroxyphenyl)ethane, tri(4-hydroxyphenyl)phenylmethane, 2,2-bis[4,4-bis(4-hydroxyphenyl)cyclohexyl]propane, 2,4-bis(4-hydroxyphenylisopropyl)phenol, tetra(4-hydroxyphenyl)methane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetra(4-[4-hydroxyphenylisopropyl]phenoxy)methane, 1,4-bis[4,4'-dihydroxytriphenyl)methyl]benzene. The branching agent of the phenolic type may be initially charged with diphenol. The branching agent of the acyl chloride may be introduced together with the acyl dichloride.

[0057] The proportion of carbonate structural units in the thermoplastic aromatic polyester carbonate can be varied as desired.The proportion of carbonate groups is preferably at most 99.9 mol%, particularly at most 80 mol%, more preferably at most 50 mol%, based on the total sum of ester groups and carbonate groups.Both the ester and carbonate moieties of the aromatic polyester carbonate can be present in the polycondensate in the form of blocks or in random distribution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0058] In a preferred embodiment, suitable polyesters are aromatic, more preferably polyalkylene terephthalates. In a particularly preferred embodiment, they are reaction products of aromatic dicarboxylic acids or their reactive derivatives, such as dimethyl esters or anhydrides, with aliphatic, cycloaliphatic or araliphatic diols, and mixtures of these reaction products.

[0059] Particularly preferred aromatic polyalkylene terephthalates contain at least 80% by weight, preferably at least 90% by weight, of terephthalic acid moieties, based on the dicarboxylic acid component, and at least 80% by weight, preferably at least 90% by weight, of ethylene glycol moieties and / or butane-1,4-diol moieties, based on the diol component.

[0060] In addition to the terephthalic acid moieties, preferred aromatic polyalkylene terephthalates may contain up to 20 mol %, preferably up to 10 mol %, of other aromatic or alicyclic dicarboxylic acid moieties having 8 to 14 carbon atoms, or aliphatic dicarboxylic acids having 4 to 12 carbon atoms, such as phthalic acid, isophthalic acid, naphthalene-2,6-dicarboxylic acid, 4,4'-diphenyldicarboxylic acid, succinic acid, adipic acid, sebacic acid, azelaic acid or cyclohexanediacetic acid moieties.

[0061] In addition to the ethylene glycol and / or butane-1,4-diol moieties, preferred aromatic polyalkylene terephthalates contain up to 20 mol %, preferably up to 10 mol %, of other aliphatic diols having 3 to 12 carbon atoms or cycloaliphatic diols having 6 to 21 carbon atoms, such as propane-1,3-diol, 2-ethylpropane-1,3-diol, neopentyl glycol, pentane-1,5-diol, hexane-1,6-diol, cyclohexane-1,4-dimethanol, 3-ethylpentane-2,4-diol, 2-methylpentane-2,4-diol, 2,2,4-tri ...

[0033] These may also contain moieties such as hexane-1,3-diol, 2-ethylhexane-1,3-diol, 2,2-diethylpropane-1,3-diol, hexane-2,5-diol, 1,4-di(β-hydroxyethoxy)benzene, 2,2-bis(4-hydroxycyclohexyl)propane, 2,4-dihydroxy-1,1,3,3-tetramethylcyclobutane, 2,2-bis(4-β-hydroxyethoxyphenyl)propane or 2,2-bis(4-hydroxypropoxyphenyl)propane (DE-A-2 407 674, DE-A-2 407 776, DE-A-2 715 932).

[0062] Particularly preferred are aromatic polyalkylene terephthalates prepared exclusively from terephthalic acid and its reactive derivatives (such as its dialkyl esters) and ethylene glycol and / or butane-1,4-diol, as well as mixtures of these polyalkylene terephthalates.

[0063] A preferred mixture of aromatic polyalkylene terephthalates comprises 1% to 50% by weight, preferably 1% to 30% by weight, of polyethylene terephthalate and 50% to 99% by weight, preferably 70% to 99% by weight, of polybutylene terephthalate.

[0064] The aromatic polyalkylene terephthalates can be prepared by known methods (see, for example, Kunststoff-Handbuch [Plastics Handbook], volume VIII, p. 695 ff., Carl-Hanser-Verlag, Munich 1973).

[0065] In one embodiment of the present invention, amorphous and / or semi-crystalline polyamides are used as polycondensation polymers. Suitable polyamides are aliphatic polyamides such as PA-6, PA-11, PA-12, PA-4,6, PA-4,8, PA-4,10, PA-4,12, PA-6,6, PA-6,9, PA-6,10, PA-6,12, PA-10,10, PA-12,12, PA-6 / 6,6 copolyamide, PA-6 / 12 copolyamide, PA-6 / 11 copolyamide, PA-6,6 / 11 copolyamide, PA-6,6 / 12 copolyamide, PA-6 / 6,10 copolyamide, PA-6,6 / 6,10 copolyamide, PA-4, ,6 / 6 copolyamide, PA-6 / 6,6 / 6,10 terpolyamide, and copolyamides formed from cyclohexane-1,4-dicarboxylic acid and 2,2,4- and 2,4,4-trimethylhexamethylenediamine, aromatic polyamides such as PA-6,1, PA-6,1 / 6,6 copolyamide, PA-6,T, PA-6,T / 6 copolyamide, PA-6,T / 6,6 copolyamide, PA-6,1 / 6,T copolyamide, PA-6,6 / 6,T / 6,1 copolyamide, PA-6, T / 2-MPMDT copolyamide (2-MPMDT = 2-methylpentamethylenediamine), PA-9,T, terephthalic acid, copolyamide formed from 2,2,4- and 2,4,4-trimethylhexamethylenediamine, isophthalic acid, copolyamide formed from laurolactam and 3,5-dimethyl-4,4-diaminodicyclohexylmethane, isophthalic acid, azelaic acid and / or sebacic acid and 4,4-diaminodicyclohexylmethane, caprolactam, isophthalic acid and / or terephthalic acid and 4,4-diaminodicyclohexylmethane, copolyamides formed from caprolactam, isophthalic acid and / or terephthalic acid and isophorone diamine, copolyamides formed from isophthalic acid and / or terephthalic acid and / or further aromatic or aliphatic dicarboxylic acids, optionally alkyl-substituted hexamethylene diamines and alkyl-substituted 4,4-diaminodicyclohexylamines or copolyamides thereof, and mixtures of the aforementioned polyamides.

[0066] As polycondensation polymer it is preferred to use linear polycarbonates based exclusively on bisphenol A.

[0067] Vinyl (co)polymer The vinyl (co)polymers of the present invention are preferably polymers of one or more vinyl monomers selected from styrene, styrene derivatives, acrylonitrile, acrylic esters, acrylic ester derivatives, olefins, maleimides, and maleimide derivatives.

[0068] In the context of the present invention, vinyl (co)polymer is also understood to mean a polymer of one or more vinyl monomers which further comprises grafting active units incorporated into the polymer chain as comonomers or end groups and / or grafted onto the polymer chain. The number of these grafting active units determines the characteristic n s Determine.

[0069] Examples of suitable styrene derivatives include α-methylstyrene and ring-substituted vinyl aromatics such as p-methylstyrene and p-chlorostyrene.

[0070] Examples of acrylic acid esters and acrylic acid ester derivatives are C1-C8 alkyl (meth)acrylates such as methyl methacrylate, n-butyl acrylate, and tert-butyl acrylate, and glycidyl methacrylate.

[0071] Examples of vinyl cyanides include acrylonitrile and methacrylonitrile.

[0072] Depending on which of the manufacturing processes described below for the graft copolymer of the present invention is used, it may be necessary to use, at least in part, a vinyl monomer having a reactive group, such as a hydroxyl group, a carboxyl group, an amino group, or a group containing a double bond, such as a vinyl group, an allyl group or an acryloyl group, a carbonyl group, a nitrile group, an ester group or an epoxy group, for the coupling reaction. It is preferable to use an epoxy group, and more preferably, glycidyl methacrylate is used as at least one of the vinyl monomers. In the reaction, glycidyl methacrylate may be incorporated into the main chain of the vinyl (co)polymer by polymerization or may be grafted onto the main chain of the vinyl (co)polymer as a side group. Preferably, glycidyl methacrylate is incorporated into the main chain of the vinyl (co)polymer by polymerization.

[0073] Other suitable vinyl (co)polymers are the following (co)polymers: B.1 50% to 99% by weight, preferably 65% ​​to 85% by weight, more preferably 70% to 80% by weight, based on the (co)polymer B, of at least one monomer selected from the group comprising vinyl aromatics, ring-substituted vinyl aromatics and C1-C8 alkyl (meth)acrylates, B.2 1% to 50% by weight, preferably 15% to 35% by weight, more preferably 20% to 30% by weight, of at least one monomer selected from the group comprising vinyl cyanide and C1-C8 alkyl (meth)acrylates, relative to the (co)polymer B.

[0074] Vinyl (co)polymers are known and can be prepared, for example, by free-radical polymerization, in particular by emulsion, suspension, solution or bulk polymerization.

[0075] Polyolefins are also produced by chain polymerization, for example free radical polymerization or anionic polymerization. In this specification, alkenes are used as monomers. Another name for alkenes is olefins. The monomers may be polymerized individually or as a mixture of various monomers. Preferred monomers are ethylene, propylene, 1-butene, isobutene, 1-pentene, 1-heptene, 1-octene, and 4-methyl-1-pentene.

[0076] The polyolefin may contain up to 50% by weight, more preferably up to 30% by weight, of further vinyl comonomers, such as preferably methyl acrylate, ethyl acrylate, butyl acrylate, glycidyl methacrylate, and methyl methacrylate.

[0077] Polyolefins may be amorphous or semicrystalline. They may be linear or branched. The manufacture of polyolefins has long been known to those skilled in the art.

[0078] The polymerization may be carried out, for example, at pressures between 1 bar and 3000 bar and temperatures between 20° C. and 300° C., optionally with the use of a catalyst system. Examples of suitable catalysts include mixtures of titanium and aluminum compounds, and metallocenes.

[0079] By varying the polymerization conditions and catalyst systems, the branching, crystallinity, and density of the polyolefins can be varied over wide ranges, these means also being well known to those skilled in the art.

[0080] Preparation of the Graft Copolymer of the Invention Graft copolymerization is a technique for producing polymers in which the main chain forms the starting point for further chains of different monomer types. This thus results in a copolymer B-(A) in which several chains A formed from the further monomer types are comb-linked onto the main chain B. ns is formed, and n s indicates the number of these chains. In the context of the present invention, the main chain A is also called the backbone and the chains B are also called side chains or grafted branches.

[0081] For the present invention, the process for producing the inventive graft copolymer structure is not critical, i.e., all graft copolymerization processes known to a person skilled in the art are in principle suitable for producing such graft copolymers of the present invention, provided that they achieve the claimed product characteristics.

[0082] The person skilled in the art is particularly familiar with the following three graft copolymerization processes which are in principle suitable for the preparation of the graft copolymers of the invention, for example:

[0083] The "Up to Graft" Process: When the polymer is exposed to high-energy electromagnetic radiation (e.g., gamma radiation), free radicals are generated along the backbone, which then form the starting points for further free radical polymerization with the extension of the second polymer. Instead of high-energy electromagnetic radiation, free radical formers can also be used to generate free radicals along the backbone of the first polymer. At the high temperatures of the grafting reaction, or alternatively under the influence of higher energy electromagnetic radiation (e.g., UV radiation), such free radical formers decompose with the formation of free radicals, which can generate free radicals, for example, from the backbone of the first polymer along its main chain or at the side groups of the polymer by abstraction of hydrogen atoms, which then form the starting points for further free radical polymerization with the extension of the second polymer. Examples of preferred free radical formers are azo compounds, such as azoisobutyronitrile (AIBN), and organic or inorganic peroxides, such as dibenzoyl peroxide (DBPO), or alkali metal peroxodisulfates. Such a graft polymerization process can in principle be carried out in a solution, emulsion or suspension of the first polymer, in a melt of the first polymer, or in the first polymer in solid form: in the latter case, the monomers forming the second polymer that will form the graft branch are immersed in the solid of the first polymer and then polymerized.

[0084] In an alternative process, the existing polymer and the monomer to be added are dissolved in a non-polar solvent (e.g., dichloromethane) and treated with a Lewis acid (coinitiator). The Lewis acid then removes electrons from the polymer at multiple sites. The resulting positively charged sites then act as initiating points for cationic polymerization with the monomer to form the grafted branches.

[0085] "From Graft" Process: In this process, reactive functional groups, such as hydroxyl, carboxyl, amino or groups containing double bonds, such as vinyl, allyl or acryloyl, carbonyl, nitrile, ester or epoxy groups, are incorporated into the backbone of the first polymer along its main chain or into any side groups present. This can be done by copolymerization with monomers containing such functional groups or by subsequent chemical treatment of the backbone polymer. These reactive functional groups in the backbone polymer can then form points of attack for graft copolymerization with the construction of graft branches from monomer units. Depending on the functional groups, various polymerization processes, such as polycondensation, polyaddition or free radical, anionic or cationic polymerization, are suitable for the construction of the graft branches.

[0086] Grafting process via macromonomers: In this process, polymer blocks endowed with reactive groups both on the graft backbone and on the side chains are prepared in a first step via polymerization processes commonly known to those skilled in the art, such as polycondensation, polyaddition or free radical, anionic or cationic polymerization, and these two reactive polymers (macromonomers) are chemically coupled to each other in a second step with the formation of a graft copolymer.

[0087] The chemical coupling reaction can be carried out in a solution containing a suitable solvent for the two polymers to be coupled or in a melt mixture of the two polymers. Melt reactions are preferred for environmental reasons, since they do not require a solvent. Melt reactions of this kind can be carried out at temperatures above the melting temperature of the two polymers to be coupled, for example in stirred tank reactors, continuous tubular reactors equipped with mixing devices, or in commercially available compounding units, such as, preferably, twin-screw extruders, planetary roller extruders or internal kneaders, and also preferably in filmtruders.

[0088] Examples of reactive groups suitable for the coupling reaction are again hydroxyl, carboxyl, amino or groups containing a double bond, such as vinyl, allyl or acryloyl, carbonyl, nitrile, ester or epoxy groups, and the functional groups in the two polymer blocks forming the backbone and the grafted branches, respectively, in the graft copolymer must be compatible with each other in pairs so as to allow the coupling reaction, preferably in the form of a condensation or addition reaction, more preferably an addition reaction. Here, for example, a combination of hydroxyl, amino or carboxy groups as functionalization of the first polymer and epoxy groups as functionalization of the second polymer is preferred, more preferably a combination of amino or carboxy groups as functionalization of the first polymer and epoxy groups as functionalization of the second polymer. When the polycondensation polymer is a polycarbonate, polyester or polyestercarbonate, it is particularly preferred to use a combination of carboxy groups as functionalization of the first polymer and epoxy groups as functionalization of the second polymer. It is further preferred herein that the polycarbonate, polyester or polyestercarbonate is functionalized with carboxy groups and the vinyl (co)polymer is functionalized with epoxy groups.

[0089] The functional groups in the polymers forming the graft branches are preferably introduced at the ends. The macromonomers used to form the graft branches are preferably polymer blocks containing only a low proportion of multifunctionalized polymer molecules, i.e. polymer molecules having two or more reactive functional groups. The polymers used to form the graft branches particularly preferably contain a number average of 1.5 or less reactive functional groups per polymer molecule, more preferably 1.3 or less, most preferably 1.1 or less. The polymers used to form the graft branches most preferably contain only terminal functional groups. This allows the number of branch structures in the graft copolymer to be minimized and prevents the formation of such undesirable structures.

[0090] The preparation of particularly preferred carboxy-terminated polycarbonates and polyestercarbonates for forming grafted branches is carried out, for example, as described in US Pat. No. 5,399,363. For the formation of carboxy-functionalized end groups, a carboxy-functionalized phenol or preferably a derivative thereof, in particular an ester of a carboxy-functionalized phenol, more preferably a tert-butyl ester of a carboxy-functionalized phenol, most preferably tert-butyl 4-hydroxybenzoate, is used as a chain terminator in the polycondensation reaction leading to the polycarbonate or polyestercarbonate, which is preferably carried out in the interfacial phosgenation of a bisphenol. In the preferred case of using a tert-butyl ester of a carboxy-functionalized phenol as an end group forming chain terminator, the terminal carboxy groups are liberated in a subsequent pyrolysis step in which isobutylene is cleaved off at temperatures above 200° C. and removed from the reaction mixture under reduced pressure, shifting the chemical equilibrium.

[0091] Whereas in the polymers disclosed in WO 2005 / 023994 only carboxy-functionalized phenols or preferably derivatives thereof, in particular esters of carboxy-functionalized phenols, are used as chain terminators, thereby forming both end-functionalized polycarbonates, for the preparation of polymer blocks particularly suitable for forming graft branches in the context of the present invention, it is recommended to use mixtures of such carboxy-functionalized phenols or preferably derivatives thereof, in particular esters of carboxy-functionalized phenols, with non-reactive functionalized phenols, such as tert-butylphenol or phenol, as chain terminators, which allows the average carboxy functionality of the resulting polycarbonate blocks to be reduced to the desired level mentioned above. In these chain terminator mixtures, the non-reactive phenols are preferably used in a molar ratio of at least 50 mol%, more preferably at least 65 mol%, more preferably at least 70 mol%, more preferably at least 75 mol%.

[0092] The preparation of the graft copolymers of the invention from these carboxy or carboxy derivative functionalized polycarbonates thus prepared can be carried out according to the method similarly described in US Pat. No. 5,399,633 by coupling with the epoxy functionality of a glycidyl methacrylate grafted polymer or with the epoxy functionality of a vinyl (co)polymer containing structural units derived from glycidyl methacrylate. When such a glycidyl methacrylate grafted polymer or a vinyl (co)polymer containing structural units derived from glycidyl methacrylate is used as a graft backbone in the preparation of a graft copolymer, the number of graft branches n in the resulting graft copolymer is scan be precisely controlled by appropriately selecting the molar ratio of glycidyl methacrylate to non-reactive vinyl monomer. The preparation of such glycidyl methacrylate modified polymers is generally known to those skilled in the art. Corresponding commercial products are commercially available under brand names such as Fine-Blend™ SAG and Fine-Blend™ SOG (both Fine-Blend Polymer Shanghai Co., Ltd.) or Lotader™ AX (Arkema).

[0093] The particularly preferred both end-grafted and centrally grafted graft copolymers can in principle be prepared by chemical coupling of macromonomers according to the same processes as described above, in this particular embodiment of the invention then a block copolymer, preferably a block copolymer consisting of blocks of vinyl (co)polymer, is used as the graft backbone.

[0094] In the preparation of double-end grafted graft copolymers, a block copolymer comprising at least three blocks is used as the graft backbone, only the two outer blocks of the block copolymer are provided with reactive functional groups according to the preferred ranges given above, and in the middle of the block copolymer serving as the graft backbone there is a portion consisting of at least one block which does not contain functional groups suitable for coupling with the graft side blocks.

[0095] In the case of the preparation of centrally grafted graft copolymers, a block copolymer comprising at least three blocks serves as the graft backbone, the two outer parts of the block copolymer each consisting of at least one block not containing a functional group suitable for coupling with the grafted side blocks, and in the central part of the block copolymer a block is used which is endowed with a reactive functional group according to the preferred ranges given above.

[0096] The reactive functionalized blocks used herein are preferably copolymers, more preferably random copolymers, of glycidyl methacrylate and at least one further vinyl monomer.

[0097] The preparation of such block copolymers suitable as graft backbones for the preparation of centrally grafted and / or both end-grafted copolymers is in principle known to the skilled artisan. To prepare such structurally defined block copolymers from blocks of different chemical composition, it is preferred to use controlled polymerization processes, often also called "living" polymerization. In principle, living anionic polymerization, living cationic polymerization, living ring-opening metathesis polymerization, living free radical polymerization, and living polycondensation are suitable. It is preferred to use living free radical polymerization processes, more preferably atom transfer radical polymerization (ATRP) or reversible addition-fragmentation chain transfer (RAFT).

[0098] Controlled ("living") polymerization is understood to mean a polymerization in which chain termination and chain transfer do not occur and the rate of chain initiation is much faster than the rate of chain extension reactions. This allows the control of molar masses with narrow distributions, as well as the production of chemically defined polymer structures, such as specific block copolymers with well-defined sequence lengths and block compositions. Block copolymers are herein constructed in multiple steps, using different monomers or monomer mixtures in each step.

[0099] Block copolymers, for example composed of structural units derived from styrene, suitable as graft backbones for the preparation of centrally grafted graft copolymers can thus be prepared, for example by one of the living polymerization processes mentioned above, for example by ATRP, by first polymerizing only styrene to the desired chain length in a first step, then polymerizing a mixture of styrene and glycidyl methacrylate onto the polymer of step 1 in a second step, and finally polymerizing pure styrene again onto the polymer of step 2 in a third step, the molar ratio of styrene and glycidyl methacrylate in step 2 making it possible to define the distance between the two graft arms in the centrally grafted graft copolymer.

[0100] Block copolymers, for example composed of structural units derived from styrene, suitable as graft backbones for the preparation of both end-grafted graft copolymers can thus be prepared in a similar manner, for example by one of the living polymerization processes mentioned above, for example by ATRP, by first polymerizing in a first step a mixture of styrene and glycidyl methacrylate to the desired chain length, then in a second step polymerizing a block of pure styrene onto the polymer of step 1, and finally, in a third step, polymerizing again a mixture of styrene and glycidyl methacrylate onto the polymer of step 2, the molar ratios of styrene and glycidyl methacrylate in steps 1 and 3 making it possible to define the distance between the two graft branches in the two end blocks. The selected proportions of styrene and glycidyl methacrylate in the two end blocks can be equal or different, the block lengths of the three blocks can likewise be configured independently of one another.

[0101] Experimental Determination of the Structural Features of the Graft Copolymers of the Invention The structural characteristics of the graft copolymers of the present invention can be determined analytically in a multi-step process.

[0102] The structural characteristics of the graft copolymers of the invention, in which the graft backbone is a vinyl (co)polymer and the side chains are polycondensation polymers, can be determined, for example, by an analytical process consisting of the following steps: 1.) Nuclear Magnetic Resonance Spectroscopy (NMR), more specifically 1 H NMR and / or 13 Determination of the chemical composition, i.e. the nature and monomer composition, of blocks A and B of a graft copolymer by C NMR. The solvent here is selected according to the specific graft copolymer. In particular, when the graft copolymers of blocks A and B have significantly different polarities, for example, B=polyolefin and A=aromatic polycarbonate, it is often necessary to carry out NMR spectroscopy at high temperatures above 60° C. in order to completely dissolve the graft copolymer. Suitable for this purpose are preferably multi-chlorinated solvents such as deuterated dichloroethane, deuterated tetrachloroethane, tetrachloromethane or deuterated di-, tri- or tetrachlorobenzene. 2.) The weight ratio x of the block of polymer A in the graft copolymer from the NMR spectroscopic data obtained in step 1 A Decision. 3.) NMR spectroscopy, more specifically from the intensity of NMR signals assigned either to the carbon atoms directly involved in the covalent graft bond or to the carbon atoms adjacent to this graft bond, or to the protons adjacent to the covalent graft bond. 1 H NMR and / or 13 Number of grafted branches, n, measured by C NMR s Decision. 4.) Determination of the molecular weight distribution of the graft copolymer by gel permeation chromatography (GPC) and the number average molecular weight M n The GPC data determined for the graft copolymer gives the value M n (A) and value M n (B) was evaluated by calibration against two polymers A and B as standards, and M n,A and M n,B is the molecular weight calibrated against standards of polymers A and B, and the value M of the graft copolymer nFrom there, the formula M n =x A M n,A +(1-x A )·M n,B In the case of GPC, too, particularly when the graft copolymers of blocks A and B have very different polarities, for example B=polyolefin and A=aromatic polycarbonate, it is often necessary to carry out the investigations at high temperatures, above 60° C., in order to completely dissolve the graft copolymer. Suitable solvents for this purpose are, for example, preferably the same as for NMR spectroscopy in step 1, although the use of deuterated solvents is not necessary for GPC. 5.) Base saponification of the polycondensed blocks or complete hydrolysis by acid or base catalysis (i.e. complete retrocleavage of the polycondensed polymer components into the monomeric units from which they are formed) and separation of the remaining intact vinyl (co)polymer blocks (graft backbones) by precipitation with subsequent washing and drying. The retrocleavage of the polycondensed polymer components into the monomeric units is preferably carried out by base saponification at elevated temperature, preferably under reflux, for example in an ethanolic potassium hydroxide solution. 6.) Determination by gel permeation chromatography (GPC) of the molecular weight distribution of the vinyl (co)polymer block (graft backbone) separated in step 5 by GPC measurements calibrated against the respective vinyl (co)polymer in the graft copolymer as standard, and the number average molecular weight M nDetermination of (B). The solvent here is selected according to the particular vinyl (co)polymer. For example, for polystyrene, polymethyl methacrylate or styrene-acrylonitrile copolymer (SAN), in each case containing glycidyl methacrylate as a grafting active site as a comonomer or termonomer unit, dichloromethane or chloroform as solvent is preferred. In these cases, GPC at room temperature is usually possible and preferred. On the other hand, for polyolefins, especially semi-crystalline polyolefins and polyolefins of high molecular weight, it is often necessary to carry out GPC at elevated temperatures above 60° C. in order to completely dissolve the graft copolymer. Suitable for this purpose are preferably polychlorinated solvents such as dichloroethane, tetrachloroethane, tetrachloromethane or di-, tri- or tetrachlorobenzene, especially ortho-dichlorobenzene. 7.) M determined in step 4 n and the value of M determined in step 6 n From the value of (B), the formula n s M n (A)=M n -M n n via (B) s M n Calculation of the value of (A) and this variable n s M n (A) is the n determined in step 3 s M by dividing by the value of n Calculation of values ​​in (A).

[0103] For the determination of the structural characteristics of the graft copolymers of the invention, in which the graft backbone is a polycondensation polymer and the side chains are vinyl (co)polymers, a similar analytical process can be used that does not differ from the above process in steps 1.) to 4.), but where step 4.) is followed by the following steps: 5.) In a manner similar to that described above, base saponification or complete acid- or base-catalyzed hydrolysis of the polycondensed blocks, i.e. complete reverse cleavage of the graft backbone into its monomeric units, followed by isolation of the remaining intact vinyl (co)polymer blocks (graft arms) by precipitation with subsequent washing and drying. 6.) Determination by gel permeation chromatography (GPC) of the molecular weight distribution of the vinyl (co)polymer blocks (grafted arms) separated in step 5, by GPC measurements calibrated against the respective vinyl (co)polymers in the graft copolymer as standards, and the number average molecular weight M n Determination of (A). The solvent is selected as above. 7.) M determined in step 4 n The value of M determined in step 6 n The value of (A) and n determined in step 3 s From the value of n (B)=M n -n s M n Value M via (A) n Calculation of (B).

[0104] In the case of graft copolymers consisting of blocks of aromatic polycarbonate and blocks of polyolefin, the NMR and GPC measurements of the graft polymer and optionally the polyolefin blocks containing the graft active units are preferably carried out in (deuterated) ortho-dichlorobenzene at a temperature of 80° C.

[0105] In the case of graft copolymers consisting of blocks of aromatic polycarbonate and blocks of polymers selected from polystyrene, polymethyl methacrylate and styrene-acrylonitrile copolymers, optionally containing grafting active units, the NMR measurements are preferably carried out at room temperature in deuterated dichloromethane.

[0106] The GPC measurements of the graft copolymers are preferably carried out in dichloromethane at room temperature, and the GPC measurements of the vinyl (co)polymer blocks are carried out in tetrahydrofuran at room temperature.

[0107] Manufacturing of molding compounds The molding compound can be made from the graft copolymer of the present invention, homopolymers A and B, or further components such as polymers having similar polarity / chemical structure as homopolymers A and B, and optionally further components.

[0108] The thermoplastic molding compounds according to the invention can be prepared, for example, by mixing the individual constituents of the composition in a known manner and melt compounding and melt extrusion, preferably at temperatures between 180° C. and 320° C., particularly preferably between 200° C. and 300° C., very particularly preferably between 240° C. and 290° C., in customary apparatus, such as, for example, internal mixers, extruders and twin-screw extruders.

[0109] This process is generally referred to as compounding in the context of this application.

[0110] Thus, "moulding compound" should be understood to mean the product obtained by melt compounding and melt extruding the constituents of the composition.

[0111] The individual components of the composition can be mixed in a known manner, either sequentially or simultaneously, either at a temperature of about 20° C. (room temperature) or higher, which means, for example, that some components can be metered in through the main intake of an extruder, while the remaining components are fed later in the compounding process through a side extruder.

[0112] The resulting molding compound is further provided by the present invention.

[0113] The molding compounds of the present invention can be used to produce molded articles. They can be produced, for example, by injection molding, extrusion and blow molding processes. A further form of processing is the production of molded articles by thermoforming from previously produced sheets or films. The molding compounds of the present invention are particularly suitable for processing by extrusion, blow molding and thermoforming methods.

[0114] It is also possible to meter the components of the composition directly into the conveying extruder of an injection molding machine to produce the molding compound of the invention in the conveying extruder, which can then be processed directly into molded articles by suitable discharge of the compound into an injection mold (compounding injection molding).

[0115] The present invention therefore further provides a moulded article obtainable from the composition according to the invention or from the moulding compound according to the invention or comprising such a moulding compound.

[0116] Further embodiments of the present invention are described below:

[0117] 1. General structure B-(A) consisting of two polymer blocks A and B of different chemical composition ns wherein one of the polymers is a polycondensation polymer selected from the group consisting of polycarbonates, polyestercarbonates, polyesters, and polyamides, and the other polymer is a polymer composed of at least one vinyl monomer; (i) Number average molecular weight M of the block of polymer B n (B) is at least 13 kg / mol, as determined by a combination of gel permeation chromatography and NMR spectroscopy; (ii) The number of side chains in the graft copolymer, n s is at least 3 and not more than 15, as determined by NMR spectroscopy; (iii) Number average molecular weight M of the block of polymer A n (A) is at least 1.5 kg / mol and not more than 15 kg / mol, as determined by a combination of gel permeation chromatography and NMR spectroscopy; (iv)n s M n Multiplying by (A) will result in at least 13 kg / mol. A graft copolymer comprising:

[0118] 2. The graft copolymer of embodiment 1, wherein polymer A is selected from the group consisting of aromatic polycarbonates, aromatic polyester carbonates, and aromatic polyesters.

[0119] 3. The graft copolymer according to embodiment 1 or 2, wherein polymer A is an aromatic polycarbonate.

[0120] 4. The graft copolymer of any of the above embodiments, wherein polymer B is a polymer of one or more different vinyl monomers selected from the group consisting of styrene, styrene derivatives, acrylonitrile, acrylic esters, acrylic ester derivatives, olefins, maleimides, and maleimide derivatives.

[0121] 5. The graft copolymer of embodiment 4, wherein the vinyl monomer is selected from the group consisting of styrene, acrylonitrile, methyl methacrylate, glycidyl methacrylate, and olefins.

[0122] 6.n s The graft copolymer of any of the above embodiments, wherein N is at least 4.

[0123] 7.n s The graft copolymer of any of the above embodiments, wherein N is at least 5.

[0124] 8.M n The graft copolymer of any of the previous embodiments, wherein (A) is at least 3.0 kg / mol.

[0125] 9.M n The graft copolymer of any of the previous embodiments, wherein (B) is at least 20 kg / mol.

[0126] 10.M n The graft copolymer of any of the previous embodiments, wherein (B) is at least 23 kg / mol.

[0127] 11. Features as follows: (i) M n (B) is at least 23 kg / mol; (ii)n s is at least 5, (iii) M n (A) is at least 3.0 kg / mol; (iv)n s M n Multiplying by (A) will result in at least 13 kg / mol.

[0036] The graft copolymer of any of the above embodiments, wherein

[0128] 12.n s The graft copolymer of any of the above embodiments, wherein N is at least 6.

[0129] 13.M n The graft copolymer of any of the previous embodiments, wherein (A) is at least 4.5 kg / mol.

[0130] 14. Features as follows: (i) M n (B) is at least 23 kg / mol; (ii)n s is at least 6, (iii) M n (A) is at least 4.5 kg / mol; (iv)n s M n Multiplying by (A) will result in at least 13 kg / mol.

[0036] The graft copolymer of any of the above embodiments, wherein

[0131] 15.M n (A)·n s / [M n (B)+M n (A)·n s ] is in the range of 0.25 to 0.75.

[0132] 16.M n (A)·n s / [M n (B)+M n (A)·n s ] is in the range of 0.40 to 0.70.

[0133] 17. Features as follows: (i) M n (B) is at least 23 kg / mol; (ii)n s is at least 6, (iii) M n (A) is at least 4.5 kg / mol; (iv)n s M n Multiplying by (A) will result in at least 13 kg / mol. (v) M n (A)·n s / [M n (B)+M n (A)·n s ] is in the range of 0.40 to 0.70,

[0036] The graft copolymer of any of the above embodiments, wherein

[0134] 18.M n The graft copolymer of any of the previous embodiments, wherein (A) is at least 5.3 kg / mol.

[0135] 19.M n The graft copolymer of any of the previous embodiments, wherein (B) is at least 30 kg / mol.

[0136] 20.M n (A)·n s / [M n (B)+M n (A)·n s ] is in the range of 0.40 to 0.60.

[0137] 21.n s M n The graft copolymer of any of the previous embodiments, which when multiplied by (A) is at least 20 kg / mol.

[0138] 22.n s M n The graft copolymer of any of the previous embodiments, which when multiplied by (A) is at least 30 kg / mol.

[0139] 23.n s M n The graft copolymer of any of the previous embodiments, which when multiplied by (A) is at least 35 kg / mol.

[0140] 24.n s The graft copolymer of any of the above embodiments, wherein

[0141] 25.n s The graft copolymer of any of the above embodiments, wherein

[0142] 26.n s The graft copolymer of any of the above embodiments, wherein

[0143] 27.M n The graft copolymer of any of the previous embodiments, wherein (A) is 12 kg / mol or less.

[0144] 28.M n The graft copolymer of any of the previous embodiments, wherein (A) is 9 kg / mol or less.

[0145] 29.M n The graft copolymer of any of the previous embodiments, wherein (A) is 8 kg / mol or less.

[0146] 30.M nThe graft copolymer of any of the previous embodiments, wherein (B) is 200 kg / mol or less.

[0147] 31.M n The graft copolymer of any of the previous embodiments, wherein (B) is 100 kg / mol or less.

[0148] 32.M n The graft copolymer of any of the previous embodiments, wherein (B) is 50 kg / mol or less.

[0149] 33.n s M n The graft copolymer of any of the previous embodiments, which when multiplied by (A) is less than or equal to 120 kg / mol.

[0150] 34.n s M n The graft copolymer of any of the previous embodiments, which when multiplied by (A) is less than or equal to 80 kg / mol.

[0151] 35.n s M n The graft copolymer of any of the previous embodiments, which when multiplied by (A) is 50 kg / mol or less.

[0152] 36. A graft copolymer according to any of the above embodiments, wherein the structure of the graft copolymer is selected from both end grafted and central grafted.

[0153] 37. A graft copolymer according to any of the above embodiments, wherein the structure of the graft copolymer is centrally grafted.

[0154] 38. Use of a graft copolymer according to any of the above embodiments for reducing the interfacial tension between phases in a mixture comprising polymers A and B or a mixture of polymers with similar polarity.

[0155] 39. A polymer composition comprising polymers A and B and, as component C, a graft copolymer according to any one of embodiments 1 to 37, wherein polymers A and B have the same chemical structure as the blocks of polymers A and B in the graft copolymer corresponding to component C.

[0156] 40. The polymer composition according to embodiment 39, wherein the ratio of the mass fraction of polymer A in the polymer composition to the mass fraction of the grafted branches in the graft copolymer corresponding to component C, relative to the total of polymers A and B in the composition, is 0.6 to 1.4.

[0157] 41. The polymer composition of embodiment 40, wherein the ratio is 0.7 to 1.3.

[0158] 42. The polymer composition of embodiment 40, wherein the ratio is 0.8 to 1.2.

[0159] 43. The polymer composition according to any of embodiments 39 to 42, wherein the graft copolymer is used in a concentration of 0.1% to 20% by weight.

[0160] 44. The polymer composition according to any of embodiments 39 to 42, wherein the graft copolymer is used at a concentration of 1.0% to 10% by weight.

[0161] 45. The polymer composition according to any of embodiments 39 to 42, wherein the graft copolymer is used at a concentration of 2% by weight to 5% by weight.

[0162] 46. ​​A molding compound obtained from the composition according to any one of embodiments 39 to 45.

[0163] 47. A molded article comprising the composition of any one of embodiments 39 to 45.

[0164] 48. A molded article made from a molding compound according to embodiment 46. EXAMPLES

[0165] Simulation of interfacial tension The effect of the structure of graft copolymers formed from blocks of two different polymers A and B on the interfacial tension at the phase interface of a polymer blend composed of homopolymers A and B was investigated by computer-aided simulations. Dissipative particle dynamics simulations were used. Simulations were carried out using the open source program LAMMPS ("LAMMPS - A flexible simulation tool for particle-based materials modeling at the atomic, meso, and continuum scales", AP Thompson, HM Aktulga, R. Berger, DS Bolintineanu, WM Brown, PS Crozier, PJ in 't Veld, A. Kohlmeyer, SG Moore, TD Nguyen, R. Shan, MJ Stevens, J. Tranchida, C. Trott, SJ Plimpton, Comp Phys Comm, 271 (2022) 10817).

[0166] The steps of the simulation carried out are shown below. For reasons of language simplicity, some explanations are written in the present tense, but reference is made to the steps that were actually performed.

[0167] In dissipative particle dynamics (DPD) simulations, relatively large molecules (polymers in this case) are modeled by beads that interact through a pairwise interaction potential. A bead in a DPD simulation represents a cluster of two or more monomer units of a polymer. These beads move under the influence of interaction forces according to Newton's equations of motion. The total force acting on each individual bead is represented by the sum of conservative, dissipative, and random forces. The simulations use r as a characteristic variable, a unit of length (the "cutoff distance"), and c , m as unit of mass, k as unit of energy B T(k Bis the Boltzmann constant, T is the temperature), and the unit of time is

number

[0168] Hereafter, the beads on which the homopolymers A and B are formed will be called a and b, respectively. The same applies to the beads on which the corresponding blocks of the graft copolymer are formed. This allows the three characteristic variables (l b , l s , and n s ) provides a simplified characterization of the graft copolymer. b is herein the number of beads on which the backbone of the graft copolymer is formed and is therefore a measure of its molecular weight. s is the number of beads on which a graft branch is formed and is therefore a measure of its molecular weight. s is the number of side chains (graft branches) grafted onto the graft copolymer backbone, and in the simulation, these side chains were always grafted with an equidistant distribution over the entire graft copolymer backbone, except for three specific molecular structures (ii) to (iv) defined below. The terms "graft branch" and "side chain" are used synonymously in this specification.

[0169] A particular embodiment of such a graft copolymer that was investigated in the context of the simulation is thus a uniformly equidistantly grafted graft copolymer. In such a graft copolymer, the grafted branches are uniformly and equidistantly distributed throughout the graft copolymer backbone. This thus results in a graft copolymer of formula I sp =1+[(l b -n s ) / (n s +1)] sp (units of number of beads) gives the distance between.

[0170] In the context of the examples in this application, specific nomenclature is defined for such uniformly equidistantly grafted graft copolymers: for example, nomenclature b 31 (a4)3 represents a graft copolymer consisting of a graft copolymer backbone of 31 beads of type b, on which three blocks each formed from four beads of type a are grafted in an equidistant distribution. The structure of such a uniformly equidistantly grafted graft copolymer, which is the basis for the simulation, is called graft copolymer b 31 (a4)3 is shown in FIG. 2 as an example. Thus, the graft copolymer molecule b 31 (a4)3 consists of a total of 31 beads of type b and 3·4=12 beads of type a.

[0171] In the DPD simulations carried out in the context of the present invention, the bead sizes were chosen so that the masses of the beads of type a and b were as similar as allowed by the molecular weight of the monomer units, i.e. the molecular weights of the beads of type a and b were essentially identical. This therefore results in a graft copolymer with a mass fraction of polymer blocks A and B that essentially corresponds to the proportion of beads of type a and b in the graft copolymer. The proportion of type b beads in a graft copolymer molecule consisting of a graft copolymer backbone of polymer A and graft branches of polymer block B can be calculated by the formula x=n s l s / (l b +n s ·l s ) is calculated according to

[0172] In the context of the present invention, according to the structure of FIG. s , l s , and l b DPD simulations were carried out for different uniformly equidistantly grafted graft copolymers by systematically varying the value of .

[0173] Furthermore, the graft copolymer structure was determined by the molecular weight of the copolymer backbone, the number of graft branches, and the molecular weight of the graft branches. b =47, l s = 8, and n s While keeping σ constant at σ = 11, the grafted arms were simulated in different distributions, i.e., grafted, on the copolymer backbone. In addition to the grafted copolymer (i) with the structure shown in Figure 1, in which the grafted arms are uniformly and equidistantly distributed on the copolymer backbone ("uniformly equidistantly grafted"), I sp Graft copolymers with a distance between side chains of 1 = 1 were simulated: (ii) all 11 graft branches are completely located at one end of the graft copolymer backbone ("single-end grafting"); (iii) 5 and 6 of the total 11 graft branches are located at both ends of the graft copolymer backbone ("double-end grafting"); and (iv) all 11 graft branches are located in the center of the graft copolymer backbone of the graft copolymer ("central grafting"). The molecular structures of these three specific graft copolymers (ii)-(iv) are shown diagrammatically in Figure 1 and compared with the structure of the uniformly equidistantly grafted copolymer (i). As defined by the nomenclature above, the four graft copolymers (i)-(iv) can be described as shown below, where the brackets in each case include adjacent portions of homopolymer blocks or graft copolymer blocks. (i)b 47 (a8) 11 (ii) [b 11 (a8) 11 ]-[b 36 ] (iii) [b5(a8)5]-[b 36 ]-[b6(a8)6] (iv) [b 18 ]-[b 11 (a8) 11 ]-[b 18 ]

[0174] A simulation of the compatibilization efficiency provided by a graft copolymer formed from blocks of polymers A and B in a two-phase blend of homopolymers A and B involved the following process steps.

[0175] 1. Formation of the starting configuration of the molecule in the simulation box Process step 1 included the following two sub-steps:

[0176] 1.1 First, the Cartesian coordinates of one homopolymer molecule of type A and one B, respectively, and the graft copolymer molecule formed from blocks of polymers A and B were set through the coordinates of the beads forming these polymers. Here, the initial bond length between two beads was set to 0.2 r c During the simulation, the bond lengths change due to the influence of the interaction forces, i.e., the final bond lengths at the simulated equilibrium states do not generally correspond to the values ​​at the start of the simulation.

[0177] 1.2 A total of 162,000 DPD beads were placed in a container with dimensions 30 x 30 x 60r c 3 The molecules are distributed almost uniformly and randomly within a periodic box with 3r c -3 The bead density of 0.5r is obtained, which, according to the general expert experience, can accurately reflect the thermodynamics of the fluid. cThe starting configurations were shown with a distance tolerance of 0.01 mm. In this process step 1.2, the number of homopolymer molecules A and B was chosen to obtain equal mass concentrations for the two homopolymers, i.e. the simulation was carried out on a blend of homopolymers A and B, where the mass fraction of the homopolymer was in each case 50% by weight. The type A and B polymer molecules according to process step 1.1 were duplicated and placed respectively in different halves of the simulation box. For the two homopolymers A and B, molecules consisting of 60 beads in each case were used in the simulation. Then, the n of each structure was calculated. c = 200 graft copolymer molecules were placed near the interface between homopolymers A and B. This starting configuration accelerates the development of thermodynamic equilibrium at the interface during the DPD simulations. In each simulation, all 200 graft copolymer molecules were placed near the interface between homopolymers A and B, with n = 200 molecules selected in each case. s , l s , and l b , as well as the spatial distribution of the grafted branches on the graft scaffold.

[0178] 2. Simulation of polymer molecular dynamics up to thermodynamic equilibrium state The position and impulse of the DPD bead were calculated at discrete time interval steps in the continuous phase space, where the classical Newtonian equation of motion (4):

number

[0179] In formula (4), f i is the mass m of the other beads. i is the force acting on bead i with P i is the impulse of this bead. A stepwise numerical integration of equation (1) was carried out using the Verlet algorithm.

[0180] The force f acting on bead i by the set of other beads i is the pairwise interaction force F between bead i and each of the other beads j in the simulation box. ij As a total sum of Equation (5):

number

number

number

number

[0181] Dissipative force component

number

number

[0182] Preservative power component

number

[0183] α is the repulsion parameter between polymers A and B AB is expressed as equation (6): α AB = α AA +3.27χ AB (6) According to the Flory-Huggins parameter χ AB can be associated with.

[0184] Here, α AA and α BB is the repulsion parameter between chemically identical molecules, i.e., A and A or B and B, and α AA = α BB =25k B Tr c -1 The value of is an empirical representation of the best compressibility of the fluid. Here, α AB A higher value of β denotes a higher incompatibility of polymer types A and B, i.e., a greater repulsion.

[0185] In this application, the bonding interaction between two directly adjacent beads of the same polymer molecule is represented by a harmonic spring force

number

[0186] The simulation was run until the mean square radius of gyration of the simulation system became stationary over time, and this stationarity was chosen as the criterion for reaching an equilibrium state. 6 Further simulation steps were calculated (Δt = 0.06t dpd ). The equilibrium configuration thus generated was used in step 4 (described below) to determine the interfacial tension γ.

[0187] 3. Mapping to actual polymer systems The mapping is performed for beads of types a and b and a repulsion parameter α AB refers to a step of the simulated process assigned to a real polymer species or an oligomeric unit of a real polymer species.

[0188] In the simulation, each bead from which the simulated polymer is composed represents an oligomeric unit of the respective polymer, i.e. a structural unit formed from a number n of monomeric units. When a specific real polymer is assigned to the theoretical polymer system, a specific value n can be specified for each individual polymer, which value is different for chemically different polymers with different molar masses in the repeating units. n is determined under the basic condition that the beads of types a and b from which the simulated homopolymers and graft copolymers are composed have approximately the same volume and therefore approximately the same mass.

[0189] In the second step of the mapping, the repulsion parameter α of a particular AB polymer system is determined. AB The value of the Flory-Huggins parameter χ according to equation (6) AB Once the specific oligomeric units of each polymer A and B formed from n monomer units have been assigned to each type a and b bead in the first step of mapping, χ ABThe value of was determined using the COSMO-RS model. For this purpose, the activity coefficient of A in the mixture γ A was calculated quantum chemically for an equimolar mixture of oligomeric units formed from n monomeric units of polymers A and B via the COSMO-RS model and using the Biova COSMOtherm 2019 (Dassault Systèmes) software. This activity coefficient γ A Using equation (7):

number

[0190] In equation (7), χ A is the molar ratio of A in the mixture (hence, χ in our example) A =0.5), and V A and V B are the volumes of species A and B, and V tot =V A +V B It is.

[0191] COSMO-RS ("CONDUCTOR like Screening MOdel for Real Solvents") is a quantum chemistry-based equilibrium thermodynamic simulation method for predicting chemical potentials in fluids and is known to those skilled in the art. Details of the COSMO-RS model and its application to problems such as those in the present application are known to those skilled in the art, for example from the review article "The COSMO and COSMO-RS solvation models" by A. Klamt, WIREs Comput Mol Sci 2018, 8:e1338. doi: 10.1002 / wcms.1338 and works cited therein.

[0192] Using this methodology, two different polymer systems were assigned (mapped) and then subjected to DPD simulations. System 1: Polymer B (graft backbone) = polystyrene, Polymer A (graft branch) = bisphenol A-based polycarbonate System 2: Polymer B (graft backbone) = polypropylene, Polymer A (graft branch) = bisphenol A-based polycarbonate

[0193] For these two systems, the mapping process yielded the type a (M a ) and b(M b ) Bead α AB and molar mass values ​​were obtained and served as the basis for the simulations.

[0194] [Table 1]

[0195] Using the molar masses of type A and B beads shown in Table 1, the grafted backbone l b and graft branch l s The value of the number of beads in the grafted backbone M is multiplied by n (B) and graft branch M n It can be converted to the molar mass of (A).

[0196] 4. Determination of interfacial tension and efficiency of graft copolymers as compatibilizers from equilibrium configurations in DPD simulations The interfacial tension γ is expressed by the following equation (8):

number

[0197] Here, P xx , P yy and P zz is expressed as equation (9):

number

[0198] The interfacial tension γ0 determined in a similar manner for an equivalent blend of homopolymers A and B in the absence of graft copolymer molecules, i.e., a non-compatibilized blend, serves as a reference in determining the compatibilizer efficiency E=(1-γ / γ0) of each graft copolymer.

[0199] The resulting compatibilizer efficiencies E are shown in Tables 2 and 3 for different graft copolymer structures, where the number of side chains (n s ), the molecular weight of the skeleton M n (B), and the molecular weight M of a single side chain n (A) was changed. From this, the molecular weight of the graft copolymer (M n (B)+n s M n (A) multiplied by M n (A) s It is also possible to calculate the molar mass fraction in weight percent that the side chains make up in the graft copolymer (mass fraction of grafted branches). Simulations were performed for graft copolymers with either a polystyrene (PS, Table 2) or polypropylene (PP, Table 3) backbone. In both cases, the side chains are formed from bisphenol A-based polycarbonate.

[0200] Table 4 shows the molecular weights M n Figure 1 shows the influence of the graft structure according to the nomenclature (i)-(iv) used above, where is the same for each graft polymer system. All graft copolymers of structures (i)-(iv) now had 11 side chains. The investigations were carried out with both polystyrene and polypropylene as the graft copolymer backbone, and with bisphenol A-based polycarbonate as the side chain in all cases.

[0201] [Table 2]

[0202] [Table 3]

[0203] [Table 4]

[0204] [Table 5]

[0205] [Table 6]

[0206] [Table 7]

[0207] [Table 8]

[0208] [Table 9]

[0209] [Table 10]

[0210] The data in Tables 2 and 3 show that only the graft copolymer embodiments of the present invention exhibit increased compatibilizer efficiency in the sense of a value E=(1−γ / γ0) of at least 30.

[0211] Furthermore, the evaluation of the data in Tables 2 and 3 was nBeyond a certain value of (A), further increase in the value of this variable no longer leads to any significant further improvement in the compatibilizer efficiency in the sense of higher values ​​of E=(1-γ / γ0). This indicates that, for example, a constant M of, for example, 20.7 kg / mol n (B) and a constant n of, for example, 4 s M for all values ​​in Table 2 n It is clear from the plot of E vs. (A). However, as mentioned above, it is desirable for graft copolymers to show their effective effect at as low a molecular weight as possible. From there, it follows that in order to achieve the required balance between good compatibilizer efficiency E and good mobility in the polymer melt and therefore rapid migration to the phase interface, M n This means that (A) must be less than 15 kg / mol.

[0212] Similarly, the evaluation of the data in Tables 2 and 3 is s It is shown that beyond a certain value of E, further increase in the value of this variable no longer leads to any significant further improvement in the compatibilizer efficiency in the sense of higher values ​​of E=(1-γ / γ0). This is the case, for example, for a constant M of, for example, 20.7 kg / mol. n (B) and a constant M of, for example, 5.5 kg / mol n n for all values ​​in Table 2 with (A) s This is evident from a plot of E vs. n (B) and a constant M of, for example, 5.5 kg / mol n n for all values ​​in Table 3 with (A) s The same is true for the plot of E vs. M n For similar reasons outlined above for (A), in order to obtain a graft copolymer with good compatibilizer efficiency E and good mobility in the polymer melt, n s The upper limit of 15 is required.

[0213] The evaluation of the data in Tables 2 and 3 further involves the product M n (A)×n sBeyond a value of about 50 kg / mol for E, further increases in the value of this variable no longer result in any significant further improvement in the compatibilizer efficiency in the sense of higher values ​​of E=(1-γ / γ0). This indicates that, for example, a constant M of, for example, 20.7 kg / mol n (B) or any of the values ​​in Table 2, for example the constant M of 22.2 kg / mol n M for all values ​​in Table 3 with (B) n (A)×n s From the plot of E vs. M as well as other constants within the scope of the present invention, n This is also evident in the corresponding plot for (B) values.

[0214] Finally, evaluation of the data in Tables 2 and 3 indicates that M n Beyond a value of about 50 kg / mol for (B), further increases in the value of this variable no longer result in any significant further improvement in the compatibilizer efficiency in the sense of higher values ​​of E=(1-γ / γ0). This indicates that, for example, a constant M of, for example, 6.3 kg / mol n (A) and constant n, e.g. s M for all values ​​in Table 2 n This is evident from the plot of E against (B).

[0215] M n (B), M n (A), n s , and M n (A)×n s Above the quoted values ​​of , there is little or no improvement in the compatibilizer efficiency of the graft copolymer at equilibrium, whereas further increases in these variables characterizing the graft copolymer become an obstacle to the desired objective, minimizing the molecular weight of the graft copolymer maximizes its mobility in the polymer melt mixture, meaning that equilibrium is reached more quickly.

[0216] The data in Table 4 show that the graft copolymers with both end grafted structures and especially the central grafted structures exhibit improved compatibilizer efficiency in the sense of higher values ​​of E=(1-γ / γ0) compared to the graft copolymers with uniformly equidistant grafted structures and especially the single end grafted structures comparable in their chemical composition, number of grafted arms, and molar mass of the graft backbone and graft arms.

[0217] The number of simulation steps required to reach the equilibrium state was evaluated for some selected simulation experiments from Table 2. The results of this analysis are shown in Table 5.

[0218] [Table 11]

[0219] The data in Table 5 are n (A), M n (B), and s and therefore the molar mass M of the graft copolymer. n is higher, and the product M n (A)×n s It is observed that higher values ​​of necessitate more simulation steps to reach a steady-state equilibrium. Applied to real polymer mixtures, this means that a longer time is required until a stable distribution of the graft copolymer in the mixture and thus a stable morphology of the components, i.e. polymers A and B as well as the graft copolymer, is reached. This therefore necessitates an increase in the set residence time in the mixing unit, such as an extruder, which is often only achievable with difficulty depending on the equipment or entails other drawbacks such as thermal damage to the polymer components. Here, the factors that greatly influence the number of simulation steps required to reach a steady-state equilibrium are, firstly, the number of graft branches n s (Experiment 4 and Experiment 6),Second, M n (A), i.e., the molecular weight of the grafted branch (Experiment 4 and Experiment 9), and therefore, as a consequence, in particular the product M n(A)×n s (All data in Table 5).

[0220] Thus, from the data in Table 5, it can be seen that the n s and M n The value of (A), especially the product M n (A)×n s It can be deduced that it is desirable to choose values ​​of not higher than are absolutely necessary to achieve the desired compatibilizer efficiency E. This consideration leads to upper limits for the values ​​of these three properties, beyond which there is little or no longer any significant improvement in the compatibilizer efficiency E, but there is a sharp increase in the residence time required to reach the equilibrium state that must be established to achieve this compatibilizer efficiency E.

[0221] Corresponding investigations on the number of simulation steps to equilibrium were also carried out for preferred graft copolymers with specific graft structures ("both end grafted" and "middle grafted"). These studies showed that n s , M n (A), and M n In comparison to a "uniformly equidistantly grafted" graft copolymer with identical values ​​of (B), we found no effect of structure, i.e., the number of simulation steps to equilibrium was the same for all three different graft copolymer structures, within the accuracy of the determination of this variable.

Claims

1. General structure B-(A) consisting of two polymer blocks A and B of different chemical composition ns A graft copolymer of the formula (I), wherein one of the polymers is a polycondensation polymer selected from the group consisting of polycarbonate, polyester carbonate, polyester, and polyamide, and the other polymer is a polymer composed of at least one vinyl monomer; (i) the number average molecular weight M of the block of polymer B n (B) is at least 13 kg / mol, as determined by a combination of gel permeation chromatography and NMR spectroscopy; (ii) the number of side chains in the graft copolymer, n s is at least 3 and not more than 15, as determined by NMR spectroscopy; (iii) the number average molecular weight M of the block of polymer A n (A) is at least 1.5 kg / mol and not more than 15 kg / mol, as determined by a combination of gel permeation chromatography and NMR spectroscopy; (iv) n s To M n (A) multiplied to be at least 13 kg / mol; A graft copolymer comprising:

2. 2. The graft copolymer of claim 1, wherein polymer A is selected from the group consisting of aromatic polycarbonates, aromatic polyestercarbonates, and aromatic polyesters.

3. 3. The graft copolymer according to claim 1, wherein polymer A is an aromatic polycarbonate.

4. The graft copolymer according to any one of claims 1 to 3, wherein polymer B is a polymer of one or more different vinyl monomers selected from the group consisting of styrene, styrene derivatives, acrylonitrile, acrylic acid esters, acrylic acid ester derivatives, olefins, maleimides, and maleimide derivatives.

5. The graft copolymer of claim 4, wherein the vinyl monomer is selected from the group consisting of styrene, acrylonitrile, methyl methacrylate, glycidyl methacrylate, and olefins.

6. Features: (i) M n (B) is at least 23 kg / mol; (ii) n s is at least 6; and (iii) M n (A) is at least 4.5 kg / mol; (iv) n s To M n (A) multiplied to be at least 13 kg / mol; (v) M n (A) n s / [M n (B) + M n (A) n s ] is in the range of 0.40 to 0.70; 6. The graft copolymer according to claim 1, wherein

7. n s The graft copolymer according to any one of claims 1 to 6, wherein is 12 or less.

8. M n The graft copolymer according to any one of claims 1 to 7, wherein (B) is 200 kg / mol or less.

9. M n The graft copolymer according to any one of claims 1 to 8, wherein (A) is 12 kg / mol or less.

10. n s To M n The graft copolymer according to any one of claims 1 to 9, which, when multiplied by (A), is 80 kg / mol or less.

11. The graft copolymer according to any one of claims 1 to 10, wherein the structure of the graft copolymer is selected from both end grafted and central grafted.

12. Use of a graft copolymer according to any one of claims 1 to 11 for reducing the interfacial tension between phases in a mixture comprising polymers A and B.

13. A polymer composition comprising polymers A and B and, as component C, a graft copolymer according to any one of claims 1 to 11, wherein polymers A and B have the same chemical structure as the blocks of polymers A and B in the graft copolymer corresponding to component C.

14. 14. The polymer composition according to claim 13, wherein the ratio of the mass fraction of polymer A in the polymer composition to the mass fraction of the grafted branches in the graft copolymer corresponding to component C, relative to the total of polymers A and B in the composition, is from 0.6 to 1.

4.

15. A molded article comprising the composition of claim 13 or 14.

Citation Information

Patent Citations

  • High-toughness polypropylene / polylactic acid ion grafted copolymer and preparation method thereof

    CN108586668A

  • Polyester amide-based resin film having ready slipperiness excellent in printability and its production

    JP1997143293A

  • Method of producing and using materials which are reinforced against impact and which contain block copolymers that are obtained by means of controlled radical polymerization in the presence of nitroxides

    US20060063891A1

  • Polycarbonate graft copolymers

    US20120071606A1

  • Faucet

    US488401A